Validity of Random Triglyceride Levels in Infants Receiving Parenteral Nutrition - Bader, Mohammad Y.; Lam, Melanie A.; Munoz, Fernando; Thompson, Leslie; Kylat, Ranjit I. (Frontiers in Pediatrics, 2021)
Background: Intravenous lipid emulsions (IL) are an important part of parenteral nutrition (PN) to meet essential fatty acid (EFA) requirements and metabolic demands of neonates and preterm infants. Some critically-ill neonates may not metabolize IL effectively which can lead to hypertriglyceridemia. Risks associated with this include increased pulmonary vascular resistance, displaced bilirubins, and platelet or macrophage dysfunction. Serum triglyceride (TG) concentration is used as a marker for lipid tolerance and predictor of potential complications involved with IL administration, but the clinical significance of this is still debated. Management of TG levels with regard to timing of laboratory tests, the ideal goal range, and duration of infusion of IL varies across institutions and is not standardized. Methods: Single-center, retrospective study of newborn infants receiving parenteral nutrition (PN). Fasting and non-fasting TG levels were drawn during the same lipid infusion of 2–3g/kg/day. The primary outcome was the difference between fasting and non-fasting TG levels. Statistical assessment of continuous data was done with student t-test and nominal data was evaluated using X2-test and logistic regression. Results: Forty infants were included with mean gestational age at birth of 29.5 ± 3.4 weeks and mean birth weight of 1.3 ± 0.5 kg. Mean time between lab draws while on same IL dose was 11.6 ± 0.2 h with resulting mean fasting and non-fasting (random) TG levels 82 ± 40 mg/dL (95% CI 68.4, 97.6) and 101 ± 40 mg/dL (95% CI 88.5, 115.8), respectively. Mean difference between TG levels during lipid-free interval and during infusion was −18.6 ± 51.2 mg/dL (95% CI −35.0, −2.3; p = 0.03). Conclusion: We concluded there is no difference in the management of IL, when TG level was drawn randomly or as fasting sample. Obtaining TG level during routine lab draws is appropriate. We extrapolated that the administration of IL over 24 h will not interfere with TG level.